A Legacy Lost to the Reformed Imagination: Luther and Confessional Lutheranism on the Extent of the Atonement - Paul Anthony Hartog (Religions, 2024)
The “Young, Restless, Reformed” movement has sought to establish itself upon reformational foundations rooted within the sixteenth century. The new movement’s undertaking, however, has virtually ignored the differences between its own adherence to “limited atonement” and the developed theology of Martin Luther. Even on an academic level, the legacy of gratia universalis ensconced within confessional Lutheranism has been largely lost to the Reformed imagination. This article focuses upon relevant materials in Luther’s Lectures on Galatians (1531/1535) and his Sermon on John 1:29 (1537), as well as the pertinent statements found within early Lutheran confessions. What emerges is a Lutheran tradition that espoused both “unconditional election” and a robust form of “unlimited atonement,” a divine provision of redemption and satisfaction for all. In Lutheran theology, this provision in Christ extra nos serves as an objective foundation for confident faith. As contemporary Reformed scholars increasingly delve into the diversity of the Reformed tradition within early modernity, the distinctive Lutheran voice is another legacy worth remembering.